2003
DOI: 10.1002/nme.667
|View full text |Cite
|
Sign up to set email alerts
|

A refined non‐linear non‐conforming triangular plate/shell element

Abstract: SUMMARYA reÿned non-conforming triangular plate=shell element for geometric non-linear analysis of plates=shells using the total Lagrangian=updated Lagrangian approach is constructed in this paper based on the reÿned non-conforming element method for geometric non-linear analysis. The Allman's triangular plane element with vertex degrees of freedom and the reÿned triangular plate-bending element RT9 are used to construct the present element. Numerical examples demonstrate that the accuracy of the new element i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
(39 reference statements)
2
7
0
Order By: Relevance
“…A flat shell element with 5 degrees-of-freedom per corner node can be obtained by combining a conventional triangular membrane element with a standard 9-dof triangular bending element. On the other hand, if several elements of this type sharing the same node are coplanar, it is difficult to achieve inter-element compatibility between membrane and transverse displacements, and the assembled global stiffness matrix is singular in shell analysis due to the absence of in-plane rotation degrees-of-freedom [9][10][11][12]34]. In addition, flat shell elements with 5 degrees-of-freedom per node lack proper nodal degrees of freedom to model folded plate/shell structures, making the assembly of elements troublesome [35].…”
Section: Introductionmentioning
confidence: 99%
“…A flat shell element with 5 degrees-of-freedom per corner node can be obtained by combining a conventional triangular membrane element with a standard 9-dof triangular bending element. On the other hand, if several elements of this type sharing the same node are coplanar, it is difficult to achieve inter-element compatibility between membrane and transverse displacements, and the assembled global stiffness matrix is singular in shell analysis due to the absence of in-plane rotation degrees-of-freedom [9][10][11][12]34]. In addition, flat shell elements with 5 degrees-of-freedom per node lack proper nodal degrees of freedom to model folded plate/shell structures, making the assembly of elements troublesome [35].…”
Section: Introductionmentioning
confidence: 99%
“…Circular cylindrical shell subjected to a central point load, R = 2540mm, L = 254mm, t = 6.35mm, θ = 0.1rad, Young's modulus, E = 3.10275kN/mm 2 and Poisson's ratio, ν = 0.3 The converged solution of a 20 × 20 mesh of the 20-node hexahedron element of ANSYS is used as a reference solution for this problem. The performance of the present elementis comparable with the solutions yielded by ANSYS and the elements of Hsiao[138], and Zhang and Cheung[136]. As with the previous test problem, the distortions experienced by the element in the mesh are not distinct and hence, the advantage of US-HEXA20 element is not obvious.…”
supporting
confidence: 62%
“…A 27-element mesh of one quarter of a clamped circular plateTable 4.4 shows the dimensionless central deflection of the circular plate, w/t, of US-HEXA20 in comparison with the analytical solution of Chia[135]. The results obtained with the 20-node hexahedron element of ANSYS, the triangular plate/shell element of Zhang and Cheung[136] and the QS plate element of Pica et al[137] are also shown.The triangular plate-bending element of Zhang and Cheung[136] is a combination of Allman's triangular plate element with vertex degrees of freedom[71] and the refined non-conforming triangular plate-bending element RT9[185]. The 8-node serendipity plate element of Pica et al[137] is based on the Mindlin plate theory and is integrated using 2 × 2 quadrature rule for all bending, membrane and shear terms in the stiffness matrix.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In their work, the interelement displacement continuity was enforced in an average sense, which resulted in not only better convergence of the solution but also improvement of its accuracy. The efficiency of the RNEM has been manifested in analyses of static, dynamic, stability and geometrically nonlinear problems [23,[25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%